Utilizing Multimedia-Assisted Brain Techniques to Improve Short Story Writing Skills In 9th Grade - Faiqotur Rosidah (Future Science, 2024)
Advanced technology recently has a significant impact on all aspects of life, including education. One of the most widespread practical uses of technology in education is digital mobile in which allows users to send various digital information from anywhere, anytime, and with anyone. This technology can also be linked to social media users. Utilization of various digital platforms such as Google Classroom, Google Form, Mentimeter, Google Meet, Kahoot, Microsoft Sway, YouTube which were packaged in this linktree are the tools used in this research. This research is a Classroom Action Research with the aim of improving students' short story writing skills using BRAIN technique as the learning steps for the students. BRAIN (Brainstorming, Read, Apply, Imagine, and Name) is a strategy development of the TPACK (Technological Pedagogical Content Knowledge) proposed by Shulman. This research was conducted in two cycles with each cycle consisting of planning, action, observation and evaluation or reflection stages. The instruments used are observation sheets, documentation sheets, student's worksheets, and the students' writings in the form of short stories. There are two types of results in each cycle, group result and individual result. In the first cycle, the group results were 71% complete and the individual result was 72% completed. As for the second cycle, the group was completed 100% and the individual was 94% completed. It’s means that students have been able to write short stories according to the structure and linguistic elements. Thus, there is an increase in student learning outcomes in the form of short story texts and it can be concluded that the use of digital platforms assisted BRAIN techniques can improve writing short stories.